2022
DOI: 10.1177/13694332221120700
|View full text |Cite
|
Sign up to set email alerts
|

Wind loads characteristics of irregular shaped high-rise buildings

Abstract: Many irregular shaped high-rise buildings have been built for graceful demand of architecture or better amenity and ventilation in the world. In this study, a benchmark rectangular high-rise building model and six high-rise building models with various irregular shapes, including two T-shaped, two U-shaped, H-shaped and X-shaped, are tested in a boundary wind tunnel to investigate their wind loads characteristics. The coefficients, power spectral density and cross-correlation of base moments as well as local w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Concerning shapes with recessed bays, a few studies have investigated wind pressure behavior in H and C-shaped buildings, especially for high-rise buildings. In general, studies show that the recessed cavities of both of these building shapes have a low average influence on wind-induced loads and dynamic responses [6,24] and could even be considered negligible [24]. However, in a detailed analysis, it was found that, at normal wind incidence, the leeward cavities of H-shaped buildings have reduced crosswind excitation compared to rectangular ones [6].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning shapes with recessed bays, a few studies have investigated wind pressure behavior in H and C-shaped buildings, especially for high-rise buildings. In general, studies show that the recessed cavities of both of these building shapes have a low average influence on wind-induced loads and dynamic responses [6,24] and could even be considered negligible [24]. However, in a detailed analysis, it was found that, at normal wind incidence, the leeward cavities of H-shaped buildings have reduced crosswind excitation compared to rectangular ones [6].…”
Section: Introductionmentioning
confidence: 99%
“…Wind load is one of the main loads to be controlled when designing engineering structures; many scholars have studied the characteristics of wind load under different working conditions [4][5][6][7][8][9][10][11][12], including studies on the influence of mountain topography, height and distance on wind load [13][14][15][16][17][18]. The shape factor of wind load is an indispensable parameter when calculating wind load, and it can be obtained by three methods: field tests [19][20][21][22], wind tunnel tests [23][24][25][26] and numerical simulations [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%